Increased spinal dynorphin contributes to chronic nicotine-induced mechanical hypersensitivity in the rat - Lough, Chris (2007)
Chronic nicotine administration has been shown previously to produce mechanical hypersensitivity in the rat although the mechanism of this effect is unknown. Rats treated with chronic systemic nicotine 3.6 or 8.6 mg/kg/day for 14-21 days displayed mechanical hypersensitivity coincident with an increase of prodynorphin immunoreactivity and dynorphin content within the spinal cord. The administration of dynorphin antiserum intrathecally significantly attenuated chronic nicotine-induced mechanical hypersensitivity. Our results suggest that chronic nicotine administration produces an increase in spinal dynorphin content and release that contributes to mechanical hypersensitivity.